2018
DOI: 10.1038/s41598-018-19825-w
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for human glioblastoma using neurotropic JC virus-like particles as a gene delivery vector

Abstract: Glioblastoma multiforme (GBM), the most common malignant brain tumor, has a short period of survival even with recent multimodality treatment. The neurotropic JC polyomavirus (JCPyV) infects glial cells and oligodendrocytes and causes fatal progressive multifocal leukoencephalopathy in patients with AIDS. In this study, a possible gene therapy strategy for GBM using JCPyV virus-like particles (VLPs) as a gene delivery vector was investigated. We found that JCPyV VLPs were able to deliver the GFP reporter gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Inspired by viruses [73], virus-like particles (VLPs) of a confined nano-sized structure have been constructed for nucleic acid delivery by assembling the virus capsid proteins with cargo nucleic acids [74,75]. Previous studies reported different VLPs for mRNA [76] and pDNA delivery [77]. However, VLP production is usually required to transfect both the virus coat protein-expression plasmid and the cargo plasmid into the same host cell or bacteria [77,78,79,80].…”
Section: Natural and Synthetic Formulation Materials-induced Nuclementioning
confidence: 99%
“…Inspired by viruses [73], virus-like particles (VLPs) of a confined nano-sized structure have been constructed for nucleic acid delivery by assembling the virus capsid proteins with cargo nucleic acids [74,75]. Previous studies reported different VLPs for mRNA [76] and pDNA delivery [77]. However, VLP production is usually required to transfect both the virus coat protein-expression plasmid and the cargo plasmid into the same host cell or bacteria [77,78,79,80].…”
Section: Natural and Synthetic Formulation Materials-induced Nuclementioning
confidence: 99%
“…Additionally, modifying JCPyV into another type of VLP takes advantage of the limited infectious range of the virus and opens the door to its use as a vector in gene therapy [212]. Excitingly, this method was used more recently with success in the treatment of glioblastoma multiforme and even prostate cancer in mice [213,214]. As JCPyV is better understood as a virus and as a vector, the scientific community may see its transition from being the causative agent in disease to a contributing factor in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Viral vectors are of interest in gliomas as tumours are nearly exclusively confined to the CNS and distant metastases are rare, which complements the potential for local intratumoural spread [84]. Most recently, Chao et al employed the JC virus (JCPyV), known to naturally infect glial cells and oligodendrocytes causing fatal progressive multifocal leukoencephalopathy in AIDS patients [85]. U87MG cells were intracranially implanted into nude mice which were subsequently treated via tail vein injection with JCPyV virus-like particles (VLPs) delivering a green fluorescent protein (GFP) reporter gene as a control.…”
Section: Viral Delivery Vehiclesmentioning
confidence: 99%
“…Subsequent analysis showed distinct GFP expression at the tumour site with no GFP expression elsewhere, and in mice treated with tk-VLPs/GCV, tumour growth was significantly inhibited. VLPs were able to protect the therapeutic genes and mediate systemic delivery to the local tumour site [85].…”
Section: Viral Delivery Vehiclesmentioning
confidence: 99%